Pole piece slurry, pole piece, preparation method thereof, lithium ion secondary battery, battery module, battery pack and power-consuming device

By adding polymer additives to the lithium-ion secondary battery pole slurry and forming a one-dimensional fiber structure through shear stirring, the problem of hot press cracking of high-pressure density pole slurry is solved, and high toughness and excellent electrochemical performance are achieved The combination of .

CN115832207BActive Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210005144.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-05
Publication Date
2025-02-21
Estimated Expiration
2042-01-05

AI Technical Summary

Technical Problem

The existing high-pressure density lithium-ion secondary battery pole plates are prone to cracking during hot pressing, resulting in low yield and difficult to improve energy density.

Method used

The lithium-ion secondary battery electrode slurry containing polymer additives is used to form a one-dimensional fiber structure through shearing and stirring, which improves the flexibility of the electrode slurry and reduces the amount of binder.

Benefits of technology

The toughness of the high-pressure density electrode sheet is significantly improved, the problem of hot press cracking is avoided, and the excellent electrochemical performance is maintained, which improves the rate performance of lithium-ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115832207B_ABST
    Figure CN115832207B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a lithium-ion secondary battery pole piece slurry, a pole piece, a preparation method thereof, a lithium-ion secondary battery, a battery module, a battery pack and an electrical device. The lithium-ion secondary battery pole piece slurry comprises an electrode material and a solvent, wherein the electrode material comprises an electrode active substance and a polymer additive, wherein the polymer additive has an aspect ratio of 500:1 or more. The polymer additive is selected from polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polypyrrole (PPY) and polythiophene (PTh). The pole piece slurry can be used to prepare a high compaction density thick pole piece, which has improved toughness, does not crack during hot pressing, and the obtained battery cell has excellent electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-ion secondary batteries, and in particular, relates to a lithium-ion secondary battery pole piece slurry and a preparation method thereof, a lithium-ion secondary battery pole piece prepared using the lithium-ion secondary battery pole piece slurry and a preparation method thereof, a lithium-ion secondary battery comprising the lithium-ion secondary battery pole piece, a battery module comprising the lithium-ion secondary battery, a battery pack comprising the battery module, and an electrical device comprising the lithium-ion secondary battery, the battery module and / or the battery pack. Background Art

[0002] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can be recharged to activate the active materials after being discharged and continue to be used. The main secondary batteries on the market include nickel-metal hydride batteries, nickel-cadmium batteries, lead-acid (or lead storage) batteries, lithium-ion secondary batteries, polymer lithium-ion secondary batteries, etc.

[0003] Lithium-ion secondary batteries have been commercialized for about 30 years and were originally mainly used in consumer electronics such as cameras, laptops, and mobile phones. As people pay more and more attention to environmental issues, replacing fossil energy with clean energy is becoming an increasingly urgent need. At the same time, with the advancement of lithium-ion secondary battery technology, lithium-ion secondary batteries have rapidly entered the field of electric vehicles in recent years. With the widespread application of lithium-ion secondary batteries, high capacity and small size have become their development trend.

[0004] The positive electrode plate of a lithium-ion secondary battery usually contains an electrode active material, a conductive agent, and a binder. The electrode active material can be selected from lithium iron phosphate, lithium nickel manganese oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium cobalt oxide, etc., and the material is mainly inorganic nano or micro particles. In order to pursue high energy density of the battery cell, the amount of active particles generally exceeds 95%. The conductive agent is mostly nano carbon black particles. The active particles and the conductive agent are bonded by a binder and bonded to the surface of the metal current collector at the same time. The binder is dissolved in a solvent, mixed with the active particles and the conductive agent to form a slurry, and then coated on the surface of the metal current collector, and then dried, the solvent evaporates, and the above materials are bonded to the surface of the particles to form a bonding network.

[0005] In order to reduce the volume, high compaction density (for example, lithium iron phosphate compaction density is greater than or equal to 2.55 g / cm 3 , the compaction density of the ternary positive electrode active material is greater than or equal to 3.5g / cm 3 ) positive electrode sheet. However, after the high compaction density positive electrode sheet is rolled and hot-pressed, the corners of the sheet are prone to cracking, resulting in a high yield rate of high compaction density sheets or even the inability to produce them, and it is difficult to increase the energy density of the battery cell.

[0006] In the prior art, people have tried to add toughening agents when preparing electrode plates to improve the flexibility of the plates. However, among the toughening agents used, some toughening agents have too high boiling points and are difficult to dry during the process of preparing the plates. The residual toughening agents will cause the interface resistance to increase, affecting the electrode dynamics. Some toughening agents are difficult to dissolve in N-methylpyrrolidone (NMP) solvent and are difficult to disperse evenly during the preparation of the slurry, resulting in hard and brittle parts of the plates. At the same time, the local enrichment of the toughening agents will affect the electrode dynamics. Some toughening agents are insulating, which significantly increases the resistance of the electrode plates and affects the battery performance.

[0007] Therefore, there is still a need in the art for a high compaction density flexible pole piece that can overcome the above-mentioned defects. Summary of the invention

[0008] The inventors of the present disclosure have provided a high compaction density flexible pole piece through extensive and in-depth research, the preparation of which does not require changing the existing preparation process, and can significantly improve the toughness of the high compaction density flexible pole piece and maintain excellent electrochemical performance. Accordingly, the present disclosure also provides a slurry for preparing such a high compaction density flexible pole piece, as well as a lithium-ion secondary battery, a battery module, a battery pack and an electric device comprising such a high compaction density flexible pole piece.

[0009] According to a first aspect of the present disclosure, a lithium-ion secondary battery pole piece slurry is provided, which comprises an electrode material and a solvent, wherein the electrode material comprises an electrode active substance and a polymer additive, and the polymer additive has an aspect ratio of greater than 500:1.

[0010] In some embodiments, the aspect ratio of the polymer additive is 500:1 to 60000:1, optionally 500:1 to 50000:1.

[0011] In some embodiments, the polymer additive is selected from one or more of polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polypyrrole (PPY), polythiophene (PTh) and derivatives thereof.

[0012] In some embodiments, the electrode active material is selected from one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0013] In some embodiments, the electrode material comprises 95-99.7 parts by weight of an electrode active material and 0.1-1.0 parts by weight of a polymer additive.

[0014] In some embodiments, the electrode material further includes a conductive agent and a binder.

[0015] In some embodiments, the electrode material comprises 95-99.7 parts by weight of an electrode active material, 0.1-2.0 parts by weight of a conductive agent, 0.1-2.0 parts by weight of a binder, and 0.1-1.0 parts by weight of a polymer additive.

[0016] In some embodiments, the slurry comprises 60-90 parts by weight of the electrode material and 10-40 parts by weight of the solvent.

[0017] According to a second aspect of the present disclosure, a method for manufacturing the above-mentioned lithium-ion secondary battery pole piece slurry is provided, comprising:

[0018] mixing an electrode material with a solvent, wherein the electrode material comprises an electrode active substance and a polymer additive,

[0019] Shear stirring is performed so that the polymer additive has an aspect ratio of 500:1 or more.

[0020] The inventor of the present application unexpectedly discovered that when preparing the pole piece slurry, the added polymer additive forms a one-dimensional fiber structure under the action of shear stirring, and the high compaction density pole piece made using the slurry has excellent flexibility and does not crack during hot pressing. The one-dimensional fiber structure can also bind the electrode active material particles and the conductive agent, allowing the amount of binder (such as PVDF) to be reduced, and the thickness of the binder wrapped on the surface of the electrode active material particles to be reduced, thereby reducing the resistance to lithium ion migration, helping to improve the migration of lithium ions in the pole piece, and ultimately making the resulting lithium ion secondary battery exhibit good rate performance.

[0021] According to a third aspect of the present disclosure, a lithium-ion secondary battery electrode is provided, which includes a current collector and an electrode material located on the current collector, wherein the electrode material includes an electrode active substance and a polymer additive, and the polymer additive has an aspect ratio of 500:1 or more.

[0022] In some embodiments, the aspect ratio of the polymer additive is 500:1 to 60000:1, optionally 500:1 to 50000:1.

[0023] In some embodiments, the polymer additive is selected from one or more of polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polypyrrole (PPY), polythiophene (PTh) and derivatives thereof.

[0024] In some embodiments, the current collector is aluminum foil; the electrode active material is selected from one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0025] In some embodiments, the electrode material comprises 95-99.7 parts by weight of an electrode active material and 0.1-1.0 parts by weight of a polymer additive.

[0026] In some embodiments, the electrode material further includes a conductive agent and a binder.

[0027] In some embodiments, the electrode material comprises 95-99.7 parts by weight of an electrode active material, 0.1-2.0 parts by weight of a conductive agent, 0.1-2.0 parts by weight of a binder, and 0.1-1.0 parts by weight of a polymer additive.

[0028] According to a fourth aspect of the present disclosure, a method for preparing the above-mentioned lithium-ion secondary battery pole piece is provided, comprising applying the above-mentioned lithium-ion secondary battery pole piece slurry to a current collector.

[0029] According to a fifth aspect of the present disclosure, a lithium-ion secondary battery is provided, which includes the above-mentioned lithium-ion secondary battery pole piece.

[0030] According to a sixth aspect of the present disclosure, a battery module is provided, which includes the above-mentioned lithium-ion secondary battery.

[0031] According to a seventh aspect of the present disclosure, a battery pack is provided, comprising the above-mentioned battery module.

[0032] According to an eighth aspect of the present disclosure, there is provided an electrical device comprising at least one of the above-mentioned lithium-ion secondary battery, the above-mentioned battery module and the above-mentioned battery pack. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solution of the embodiment of the present disclosure, the following briefly introduces the drawings required for use in the embodiment of the present disclosure. Obviously, the drawings in the embodiment of the present disclosure described below are only examples, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0034] Figure 1 It is a schematic diagram of one embodiment of the lithium ion secondary battery of the present application.

[0035] Figure 2 yes Figure 1 An exploded view of a lithium-ion secondary battery is shown.

[0036] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0037] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0038] Figure 5 yes Figure 4 Exploded view of the battery pack shown.

[0039] Figure 6 This is a schematic diagram of one embodiment of a device using the lithium ion secondary battery of the present application as a power source.

[0040] Figure 7 This is the SEM image of the electrode prepared in Comparative Example 1.

[0041] Figure 8 This is the SEM image of the electrode prepared in Comparative Example 2.

[0042] Fig. 9 This is a SEM image of the electrode prepared in Example 1.

[0043] Fig.10 This is the SEM image of the electrode prepared in Example 7.

[0044] Description of reference numerals:

[0045] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0046] The following detailed description and drawings of the embodiments of the present disclosure are used to illustrate the principles of the present disclosure, but cannot be used to limit the scope of the present disclosure, that is, the present disclosure is not limited to the described embodiments.

[0047] "Scope" disclosed herein is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope defined in this way can include or exclude end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present disclosure, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] In the present disclosure, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0049] In the present disclosure, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0050] In the present disclosure, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0051] In the present disclosure, unless otherwise specified, the terms "include" and "comprising" mentioned herein may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or comprised, or may only include or comprise the listed components.

[0052] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive numbers, and "several" in "one or several" means two or more. In the description of this article, the terms "first", "second", "third", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0053] In the description herein, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0054] Lithium-ion secondary battery electrode slurry

[0055] The lithium-ion secondary battery pole piece slurry disclosed in the present invention comprises an electrode material and a solvent, wherein the electrode material comprises an electrode active substance and a polymer additive, and the polymer additive has an aspect ratio of 500:1 or more.

[0056] The electrode active material may be selected from positive electrode active materials. The positive electrode active material includes, but is not limited to, one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. Lithium iron phosphate may be, for example, LiFePO4 (LFP). Lithium nickel cobalt manganese oxide may be, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.5 Co 0.3 Mn 0.2 O2(NCM532).

[0057] The polymer additive is selected from one or more of polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polypyrrole (PPY) and polythiophene (PTh) and their derivatives. The derivative of polythiophene can be, for example, a polymer of 3,4-ethylenedioxythiophene (PEDOT). Without being limited to any particular theory, the applicant believes that these polymer additives can achieve a fiber structure through external shearing, reduce the particle sliding resistance during winding and sheeting, and solve the problem of hot pressing cracking of high compaction density pole pieces; at the same time, reduce the amount of PVDF, reduce the film thickness of PVDF on the surface of the active particles, improve the diffusion impedance of lithium ions in the active particles, and improve the dynamics of the pole piece.

[0058] The molecular weight of the polymer additive is not particularly limited, as long as it can form a high aspect ratio fiber through shear stirring. As a non-limiting example, the weight average molecular weight of PTFE can be 2,000,000-4,000,000 g / mol, optionally 2,500,000-3,500,000 g / mol, such as 3,000,000 g / mol; the weight average molecular weight of PEO can be 50,000-200,000 g / mol, optionally 80,000-150,000 g / mol, such as 100,000 g / mol; the weight average molecular weight of PAN can be 150,000-350,000 g / mol, optionally 200,000-300,000 g / mol, such as 100,000 g / mol; For example, 250,000 g / mol; the weight average molecular weight of PVA can be 30,000-70,000 g / mol, optionally 40,000-60,000 g / mol, for example, 50,000 g / mol; the weight average molecular weight of PPY can be 50,000-200,000 g / mol, optionally 80,000-150,000 g / mol, for example, 100,000 g / mol; the weight average molecular weight of PTh can be 50,000-200,000 g / mol, optionally 80,000-150,000 g / mol, for example, 100,000 g / mol. In the present disclosure, the polymer additive is sheared and stirred to form a high aspect ratio polymer fiber.The aspect ratio of the polymer fiber can be 500:1 to 60000:1, for example, 500:1, 600:1, 700:1, 800:1, 900:1, 1000:1, 1500:1, 2000:1, 2500:1, 3000:1, 3500:1, 4000:1, 4500:1, 5000:1, 5500:1, 6000:1, 6500:1, 7000:1 00:1,7500:1,8000:1,8500:1,9000:1,9500:1,10000:1,15000:1,16000:1,17000:1,18000:1,19000:1,20000:1,21000:1,22000:1,23000:1,24000:1,25000:1,26000:1,2 7000:1, 28000:1, 29000:1, 30000:1, 31000:1, 32000:1, 33000:1, 34000:1, 35000:1, 36000:1, 37000:1, 38000:1, 39000:1, 40000:1, 41000:1, 42000:1, 43000:1, 44000:1, 45 000:1, 46000:1, 47000:1, 48000:1, 49000:1, 50000:1, 51000:1, 52000:1, 53000:1, 54000:1, 55000:1, 56000:1, 57000:1, 58000:1, 59000:1, 60000:1 and ranges with any two of the above ratios as endpoints. Fiber aspect ratio refers to the ratio of fiber length to diameter.

[0059] The electrode material may further include a conductive agent and a binder. Non-limiting examples of conductive agents may include one or more of superconducting carbon, carbon black (e.g., acetylene black, ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Non-limiting examples of binders may include one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0060] The solvent may be a conventional solvent for preparing a lithium-ion secondary battery electrode slurry, including solvents known in the prior art and solvents to be developed in the future, such as N-methylpyrrolidone (NMP).

[0061] In some embodiments, the electrode material comprises 95-99.7 parts by weight of an electrode active material and 0.1-1.0 parts by weight of a polymer additive. Although the content of the electrode active material in the electrode material is not limited to the above range, the amount within the range can ensure that the electrode active material is used at the highest amount and the energy density of the battery cell is maximized. In some embodiments, the weight parts of the electrode active material are 95-99.7 parts by weight, for example, 95 parts by weight, 95.5 parts by weight, 96 parts by weight, 96.5 parts by weight, 97 parts by weight, 97.5 parts by weight, 98 parts by weight, 98.5 parts by weight, 99 parts by weight, 99.1 parts by weight, 99.2 parts by weight, 99.3 parts by weight, 99.4 parts by weight, 99.5 parts by weight, 99.6 parts by weight, 99.7 parts by weight, and a range consisting of any two of the above values ​​as endpoints. In some embodiments, the weight portion of the polymer additive is 0.1-1.0 weight portion, for example 0.1 weight portion, 0.2 weight portion, 0.3 weight portion, 0.4 weight portion, 0.5 weight portion, 0.6 weight portion, 0.7 weight portion, 0.8 weight portion, 0.9 weight portion, 1.0 weight portion and a range consisting of any two of the above values ​​as endpoints. In some embodiments, the electrode material further comprises a conductive agent and a binder. In some embodiments, the electrode material comprises 95-99.7 weight portions of electrode active material, 0.1-2.0 weight portions of conductive agent, 0.1-2.0 weight portions of binder and 0.1-1.0 weight portion of polymer additive. In some embodiments, the weight part of the conductive agent is 0.1-2.0 weight parts, for example, 0.1 weight part, 0.2 weight part, 0.3 weight part, 0.4 weight part, 0.5 weight part, 0.6 weight part, 0.7 weight part, 0.8 weight part, 0.9 weight part, 1.0 weight part, 1.1 weight part, 1.2 weight parts, 1.3 weight parts, 1.4 weight parts, 1.5 weight parts, 1.6 weight parts, 1.7 weight parts, 1.8 weight parts, 1.9 weight parts, 2.0 weight parts and a range consisting of any two of the above values ​​as endpoints. In some embodiments, the weight part of the binder is 0.1-2.0 weight parts, for example, 0.1 weight part, 0.2 weight part, 0.3 weight part, 0.4 weight part, 0.5 weight part, 0.6 weight part, 0.7 weight part, 0.8 weight part, 0.9 weight part, 1.0 weight part, 1.1 weight part, 1.2 weight part, 1.3 weight part, 1.4 weight part, 1.5 weight part, 1.6 weight part, 1.7 weight part, 1.8 weight part, 1.9 weight part, 2.0 weight part and a range consisting of any two of the above values ​​as endpoints.

[0062] In some embodiments, the slurry comprises 60-90 parts by weight of electrode material and 10-40 parts by weight of solvent. Although the amount of electrode material and solvent is not limited to the above range, the amount of electrode material and solvent within the above range can ensure that the electrode active material, conductive agent, binder and polymer fiber additive are uniformly dispersed in the solvent. In some embodiments, the weight parts of electrode material are 65-85 parts by weight, and 70-80 parts by weight can be selected, for example, 75 parts by weight. In some embodiments, the weight parts of solvent are 15-35 parts by weight, and 20-30 parts by weight can be selected, for example, 25 parts by weight.

[0063] The lithium-ion secondary battery pole piece slurry disclosed in the present invention may also include other optional auxiliary agents, such as a thickener (such as sodium carboxymethyl cellulose CMC-Na), a PTC thermistor material, and the like.

[0064] In some embodiments, the lithium ion secondary battery pole piece slurry disclosed herein is a positive pole piece slurry for preparing a positive pole piece of a lithium ion secondary battery, which comprises a positive electrode material and a solvent.

[0065] The present disclosure also provides a method for manufacturing the above-mentioned lithium-ion secondary battery electrode slurry, which includes: mixing electrode materials and polymer additives with a solvent, wherein the electrode materials include electrode active substances and polymer additives, and performing shear stirring to allow the polymer additive to obtain an aspect ratio of 500:1 or more.

[0066] Shear stirring can be performed using a shear stirring device known in the art and developed in the future, such as a dual planetary stirring device. As a non-limiting example, the dispersion disk speed of the dual planetary stirring device can be 1000-3000 rpm, optionally 1500-2000 rpm, and the kneading disk speed can be 10-30 rpm, optionally 15-25 rpm. As a non-limiting example, the stirring temperature can be controlled at 25-30° C., and the stirring time can be 60-130 minutes, optionally 70-120 minutes, 80-110 minutes, or 90-100 minutes.

[0067] Lithium-ion secondary battery electrode

[0068] The above-mentioned lithium-ion secondary battery pole piece slurry is coated on the current collector, and after drying, cold pressing and other processes, the lithium-ion secondary battery pole piece can be obtained.

[0069] Thus, the present disclosure provides a lithium ion secondary battery pole piece, which includes a current collector and an electrode material located on the current collector, wherein the electrode material includes an electrode active substance and a polymer additive, and the polymer additive has an aspect ratio of greater than 500: 1. In some embodiments, the electrode material further includes a conductive agent and a binder.

[0070] The electrode active material, conductive agent, binder and polymer additive are as described above.

[0071] The current collector may be a positive electrode current collector. The positive electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and copolymers thereof).

[0072] Lithium-ion secondary battery

[0073] The present disclosure also provides a lithium-ion secondary battery, which includes the above-mentioned lithium-ion secondary battery pole piece.

[0074] Lithium-ion secondary batteries usually include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, etc. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0075] In some embodiments, in the lithium-ion secondary battery of the present disclosure, the positive electrode plate is made of the lithium-ion secondary battery plate slurry of the present disclosure.

[0076] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer contains a negative electrode active material, a conductive agent and a binder.

[0077] The negative electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be a copper foil, a silver foil, an iron foil, or a foil composed of an alloy of the above metals. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer, and may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material base layer (such as a base layer made of materials such as polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and copolymers thereof).

[0078] The negative electrode active material is selected from one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. As an example, the conductive agent may include one or more of superconducting carbon, carbon black (e.g., acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers. As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). As an example, the binder may include one or more of styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0079] The separator separates the positive electrode side from the negative electrode side of the lithium-ion secondary battery, and provides selective permeation or blocking for substances of different types, sizes and charges in the system. For example, the separator can insulate electrons, physically isolate the positive and negative active substances of the lithium-ion secondary battery, prevent internal short circuits and form an electric field in a certain direction, and enable ions in the battery to pass through the separator and move between the positive and negative electrodes. In one embodiment of the present disclosure, the material used to prepare the separator may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0080] In the lithium ion secondary battery of the present disclosure, the electrolyte may be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). In some embodiments, the electrolyte uses an electrolyte. The electrolyte includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt may be selected from LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bisfluorosulfonyl imide), LiTFSI (lithium bistrifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro oxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluoro oxalate phosphate) and LiTFOP (lithium tetrafluoro oxalate phosphate) One or more. In one embodiment of the present disclosure, the solvent may be selected from one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE). In one embodiment of the present disclosure, based on the total weight of the electrolyte, the content of the solvent is 60-99 wt%, such as 65-95 wt%, or 70-90 wt%, or 75-89 wt%, or 80-85 wt%. In one embodiment of the present disclosure, based on the total weight of the electrolyte, the content of the electrolyte is 1-40 wt%, such as 5-35 wt%, or 10-30 wt%, or 11-25 wt%, or 15-20 wt%.

[0081] In the lithium-ion secondary battery of the present disclosure, the electrolyte may optionally contain additives. For example, the additives may include one or more of the following: negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0082] In one embodiment of the present disclosure, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly / bare cell by a winding process or a lamination process.

[0083] In one embodiment of the present disclosure, the lithium-ion secondary battery may include an outer packaging, which can be used to encapsulate the above-mentioned electrode assembly and electrolyte / electrolyte. In some embodiments, the outer packaging of the lithium-ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. In other embodiments, the outer packaging of the lithium-ion secondary battery can be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0084] The lithium-ion secondary battery of the present disclosure may be in a cylindrical, square, or other arbitrary shapes. Figure 1 The lithium ion secondary battery 5 is a square structure as an example. Figure 2 Shows Figure 1 The exploded view of the lithium-ion secondary battery 5 is shown in FIG. 5 . The outer package may include a shell 51 and a top cover assembly 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly is encapsulated in the receiving cavity, and the electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the lithium-ion secondary battery 5 can be one or more.

[0085] Battery modules, battery packs and power-consuming devices

[0086] In one embodiment of the present disclosure, several lithium-ion secondary batteries may be assembled together to form a battery module, which includes two or more lithium-ion secondary batteries described in the present disclosure, and the specific number depends on the application of the battery module and the parameters of a single battery module.

[0087] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of lithium-ion secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of lithium-ion secondary batteries 5 may be fixed by fasteners.

[0088] Optionally, the battery module 4 may further include a housing having a housing space, and the plurality of lithium-ion secondary batteries 5 are housed in the housing space.

[0089] In one embodiment of the present disclosure, two or more of the above-mentioned battery modules can be assembled into a battery pack, and the number of battery modules contained in the battery pack depends on the application of the battery pack and the parameters of the individual battery modules. The battery pack may include a battery box and a plurality of battery modules disposed in the battery box, and the battery box includes an upper box body and a lower box body, and the upper box body can cover the lower box body and match well with it to form a closed space for accommodating the battery modules. Two or more battery modules can be arranged in the battery box in a desired manner.

[0090] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0091] In one embodiment of the present disclosure, the electric device of the present disclosure includes at least one of the lithium ion secondary battery, battery module or battery pack of the present disclosure, and the lithium ion secondary battery, battery module or battery pack can be used as a power source of the electric device, and can also be used as an energy storage unit of the electric device. The electric device includes but is not limited to mobile digital devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0092] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the power consumption device for high power and high energy density, a battery pack or a battery module can be used.

[0093] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a lithium-ion secondary battery may be used as a power source.

[0094] Technical Effects

[0095] The inventors of the present disclosure unexpectedly discovered that by adding a polymer additive when preparing the electrode slurry, the polymer additive material can be formed into a one-dimensional fiber structure through appropriate shear stirring, which can provide good flexibility for the electrode active layer made of the slurry, thereby improving the flexibility of the high compaction density electrode. After winding and hot pressing, the electrode will not crack at the corners.

[0096] Surprisingly, by forming the polymer additive into a one-dimensional fiber structure, the excellent electrochemical performance of the resulting electrode is maintained. Without being limited to any particular theory, the applicant believes that because these polymer materials contain polar functional groups, they can well infiltrate lipid electrolytes, thereby improving the rate performance of the electrode. At the same time, the fiber structure can bind the electrode active material particles and the conductive agent, allowing the amount of binder (such as PVDF) to be reduced, and reducing the thickness of the binder wrapped on the surface of the electrode active material particles, thereby reducing the resistance to lithium ion migration, helping to improve the migration of lithium ions in the electrode, and ultimately showing good rate performance.

[0097] In addition, the method for preparing pole piece slurry and pole piece disclosed in the present invention can utilize existing process equipment and does not require major changes to the existing process route, which is conducive to cost savings.

[0098] Example

[0099] The present invention will be further described in detail below in conjunction with examples. It should be understood that these examples are only for illustrative purposes and are not intended to limit the scope of the present invention.

[0100] In the following examples and comparative examples, the reagents, materials and instruments used, unless otherwise specified, can be obtained through commercial purchase or synthetic routes.

[0101] Lithium iron phosphate (LFP), NCM532 (LiNi 0.5 Co 0.3 Mn 0.2 O2) and graphite are manufactured by B&T New Materials Group Co., Ltd.; conductive carbon (SP) is manufactured by Shanghai Kain Chemical Co., Ltd.; and the electrolyte is manufactured by Shenzhen Xinzhoubang Technology Co., Ltd.

[0102] The stirring equipment is a 10L double planetary stirring equipment produced by Honggong Technology Co., Ltd. The stirring conditions are as follows: the temperature is controlled at 25-30°C; the stirring speed is 1000-3000rpm for the dispersion disk and 10-30rpm for the kneading disk; the stirring time is 60-130min.

[0103] The measurement method of fiber aspect ratio is: first characterize the morphology and particle radius (R) of pure polymer material particles by SEM, and then characterize the radius (r) of polymer material in the pole piece by SEM. According to the principle of constant volume, the fiber aspect ratio can be calculated:

[0104] The weight of the electrode refers to the weight per unit area (1540.25mm) after the electrode is dried. 2The test method is: after the electrode is dried, a punching machine is used to punch out an area of ​​1540.25mm 2 The electrode disc is weighed and its mass is recorded as M1. The mass of pure aluminum foil corresponding to this area is M2, so the weight of the electrode is M1-M2. The way to adjust the weight of the electrode in extrusion coating is to adjust the gap between the extruder head and the current collector. The larger the gap, the greater the weight of the electrode.

[0105] The test method for simulating hot pressing is as follows: (1) Cut a 1.5 cm × 15 cm electrode standard sample; (2) Bend the electrode and use a 2 kg roller to press the bend of the electrode to observe whether the crease is light-transmissive.

[0106] Comparative Example 1

[0107] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), and conductive carbon SP are mixed in a weight ratio of 97.4:1.8:0.8 in an N-methylpyrrolidone solvent system, and then coated on an Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain positive electrode sheets of different gram weights (see Table 8).

[0108] Compaction density control:

[0109] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain pole pieces with different compaction densities: the compaction density under 1T pressure was 2.4g / cm 3 , the compaction density under 3T pressure is 2.55g / cm 3 , the compaction density under 8T pressure is 2.6g / cm 3 .

[0110] Figure 7 This is a SEM characterization picture of the electrode piece prepared in Comparative Example 1. It can be seen that the electrode material on the aluminum foil exists in the form of particle accumulation.

[0111] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0112] Comparative Example 2

[0113] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and hydroxyapatite were mixed in a weight ratio of 97.4:1.6:0.8:0.2 in an N-methylpyrrolidone solvent system, and then coated on an Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain positive electrode sheets of different gram weights (see Table 8).

[0114] Compaction density control:

[0115] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain pole pieces with different compaction densities: the compaction density under 1T pressure was 2.4g / cm 3 , the compaction density under 2.5T pressure is 2.55g / cm 3 , the compaction density under 7T pressure is 2.6g / cm 3 .

[0116] Figure 8 This is a SEM image of the electrode prepared in Comparative Example 2, in which the hydroxyapatite fiber structure can be observed.

[0117] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0118] Example 1

[0119] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PTFE are fully kneaded in an N-methylpyrrolidone solvent system according to the weight ratio shown in Table 1, and coated on an Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain a positive electrode sheet. By adjusting the shear stirring conditions, PTFE is formed into fibers with different aspect ratios. The aspect ratios are shown in Table 8.

[0120] Table 1

[0121]

[0122]

[0123] Compaction density control:

[0124] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain the following compaction density of the pole piece: the compaction density under 65T pressure is 2.6g / cm 3 .

[0125] Fig. 9 This is a SEM image of the pole piece prepared in Example 1, from which the PTFE fiber structure can be observed.

[0126] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0127] Example 2

[0128] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PEO (polyethylene oxide) are mixed in the N-methylpyrrolidone solvent system according to the weight ratio shown in Table 2, and then coated on Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried and cold pressed to obtain a positive electrode sheet. By adjusting the shear stirring conditions, PEO is formed into fibers with different aspect ratios. The aspect ratio is shown in Table 8.

[0129] Table 2

[0130] serial number Lithium Iron Phosphate PVDF SP PEO 2-1 97.4 1.6 0.8 0.2 2-2 97.4 1.2 0.8 0.6 2-3 97.4 0.8 0.8 1.0

[0131] Compaction density control:

[0132] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain the following compaction density of the pole piece: the compaction density under 70T pressure is 2.6g / cm 3 .

[0133] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0134] Example 3

[0135] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PAN (polyacrylonitrile) were mixed in the N-methylpyrrolidone solvent system according to the weight ratio shown in Table 3, and then coated on Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain a positive electrode sheet. By adjusting the shear stirring conditions, PAN was formed into fibers with different aspect ratios. The aspect ratios are shown in Table 8.

[0136] Table 3

[0137] serial number Lithium Iron Phosphate PVDF SP PAN 3-1 97.4 1.6 0.8 0.2 3-2 97.4 1.2 0.8 0.6 3-3 97.4 0.8 0.8 1.0

[0138] Compaction density control:

[0139] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain the following compaction density of the pole piece: the compaction density under 70T pressure is 2.6g / cm 3 .

[0140] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0141] Example 4

[0142] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PVA (polyvinyl alcohol) are mixed in the N-methylpyrrolidone solvent system according to the weight ratio shown in Table 4, and then coated on Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried and cold pressed to obtain a positive electrode sheet. By adjusting the shear stirring conditions, PVA is formed into fibers with different aspect ratios. The aspect ratios are shown in Table 8.

[0143] Table 4

[0144] serial number Lithium Iron Phosphate PVDF SP PVA 4-1 97.4 1.6 0.8 0.2 4-2 97.4 1.2 0.8 0.6 4-3 97.4 0.8 0.8 1.0

[0145] Compaction density control:

[0146] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain the following compaction density of the pole piece: the compaction density under 70T pressure is 2.6g / cm 3 .

[0147] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0148] Example 5

[0149] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PPY (polypyrrole) were mixed in the N-methylpyrrolidone solvent system according to the weight ratio shown in Table 5, and then coated on Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain a positive electrode sheet. By adjusting the shear stirring conditions, PPY was formed into fibers with different aspect ratios. The aspect ratios are shown in Table 8.

[0150] Table 5

[0151] serial number Lithium Iron Phosphate PVDF SP PPY 5-1 97.4 1.6 0.8 0.2 5-2 97.4 1.2 0.8 0.6 5-3 97.4 0.8 0.8 1.0

[0152] Compaction density control:

[0153] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain the following compaction density of the pole piece: the compaction density under 70T pressure is 2.6g / cm 3 .

[0154] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0155] Example 6

[0156] The positive electrode active material lithium iron phosphate, binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PTh were mixed in N-methylpyrrolidone solvent system according to the weight ratio shown in Table 6, and then coated on Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried and cold pressed to obtain a positive electrode sheet. By adjusting the shear stirring conditions, PTh was formed into fibers with different aspect ratios. The aspect ratios are shown in Table 8.

[0157] Table 6

[0158]

[0159]

[0160] Compaction density control:

[0161] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain the following compaction density of the pole piece: the compaction density under 75T pressure is 2.6g / cm 3 .

[0162] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0163] Comparative Example 3

[0164] The positive electrode active material lithium nickel cobalt manganese oxide (NCM532), the binder PVDF (polyvinylidene fluoride), and the conductive carbon SP were mixed in a weight ratio of 98.2:1:0.8 in an N-methylpyrrolidone solvent system, and then coated on an Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain positive electrode sheets of different gram weights (see Table 8).

[0165] Compaction density control:

[0166] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain pole pieces with different compaction densities: the compaction density under 15T pressure was 3.5g / cm 3 , the compaction density under 25T pressure is 3.55g / cm 3 .

[0167] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0168] Example 7

[0169] The positive electrode active material lithium nickel cobalt manganese oxide (NCM532), binder PVDF (polyvinylidene fluoride), conductive carbon SP, and additive PTFE were fully stirred and mixed in an N-methylpyrrolidone solvent system according to the weight ratio shown in Table 7, and then coated on an Al foil (length 100m, width 350mm, thickness 15μm) by extrusion coating or transfer coating, dried, and cold pressed to obtain a positive electrode sheet.

[0170] Table 7

[0171]

[0172]

[0173] Compaction density control:

[0174] The cold press (Xingtai Nano Rolling Technology Co., Ltd.) was used to adjust the pressure to obtain pole pieces with different compaction densities: the compaction density under 10T pressure was 3.5g / cm 3 , the compaction density under 20T pressure is 3.55g / cm 3 .

[0175] The pole piece was subjected to a simulated hot pressure test to observe the cracking of the pole piece (see Table 8).

[0176] Fig.10 This is a SEM image of the pole piece prepared in Example 7, from which the PTFE fiber structure can be observed.

[0177] Lithium-ion secondary battery preparation

[0178] The negative electrode active material artificial graphite, the conductive agent acetylene black and the binder PVDF were fully stirred in N-methylpyrrolidone at a weight ratio of 96:2:2, coated on a Cu foil, dried and cold pressed to obtain a negative electrode sheet.

[0179] Stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play an isolating role, and wind them to obtain a bare cell. Place the bare cell in an outer package, inject the prepared electrolyte and package it. The electrolyte uses ethylene carbonate and dimethyl carbonate as solvents and lithium hexafluorophosphate as lithium salt. Use a polyethylene (PE) porous polymer film as a separator.

[0180] Battery rate test

[0181] A charge and discharge tester (Shenzhen Xinwei Electronics Co., Ltd.) was used to measure the capacity retention rate of the battery cells at different charge and discharge rates (0.33C, 1C, 3C, and 6C).

[0182] Lithium iron phosphate battery test conditions:

[0183] The prepared battery was placed at a constant temperature of 25°C for 30 minutes, charged at a constant current of 0.33C to 3.75V, charged at a constant voltage with a cutoff current of 0.05C, and allowed to stand for 30 minutes; discharged at a constant current of 0.33C to 2.5V, and the discharge capacity C0 was recorded.

[0184] Charge at 1C constant current to 3.75V, charge at constant voltage with a cut-off current of 0.05C, let stand for 30 minutes, discharge at 1C to 2.5V, and record the discharge capacity C1. The 1C discharge capacity retention rate is (C1 / C0)×100%.

[0185] Charge at 3C constant current to 3.75V, charge at constant voltage with a cutoff current of 0.05C, let stand for 30 minutes, discharge at 3C to 2.5V, and record the discharge capacity C2. The 3C discharge capacity retention rate is (C2 / C0)×100%.

[0186] Charge at 6C constant current to 3.75V, charge at constant voltage with a cutoff current of 0.05C, let stand for 30 minutes, discharge at 6C to 2.5V, and record the discharge capacity C3. The 6C discharge capacity retention rate is (C3 / C0)×100%.

[0187] Ternary NCM532 battery test conditions:

[0188] The prepared battery was placed at a constant temperature of 25°C for 30 minutes, charged at a constant current of 0.33C to 4.2V, charged at a constant voltage with a cutoff current of 0.05C, and allowed to stand for 30 minutes; discharged at a constant current of 0.33C to 2.5V, and the discharge capacity C0 was recorded.

[0189] Charge at 1C constant current to 4.2V, charge at constant voltage with a cut-off current of 0.05C, let stand for 30 minutes, discharge at 1C to 2.5V, and record the discharge capacity C1. The 1C discharge capacity retention rate is (C1 / C0)×100%.

[0190] Charge at 3C constant current to 4.2V, charge at constant voltage with a cut-off current of 0.05C, let stand for 30 minutes, discharge at 3C to 2.5V, and record the discharge capacity C2. The 3C discharge capacity retention rate is (C2 / C0)×100%.

[0191] Charge at 6C constant current to 4.2V, charge at constant voltage with a cutoff current of 0.05C, let stand for 30 minutes, discharge at 6C to 2.5V, and record the discharge capacity C3. The 6C discharge capacity retention rate is (C3 / C0)×100%.

[0192] Table 8

[0193]

[0194]

[0195]

[0196] It can be seen from the above table that compared with Comparative Examples 1 and 3 in which no fiber additives are added, the presence of high aspect ratio polymer fiber additives prevents the obtained pole piece from cracking during hot pressing at high compaction density. By adding polymer fiber additives to obtain high aspect ratio fibers, not only can high compaction density thick electrodes be obtained, but the prepared battery cells still maintain a very high capacity retention rate. Although the hydroxyapatite in Comparative Example 2 is also fibrous, the corresponding high compaction density thick pole piece cracks during hot pressing. In other words, under conditions of higher gram weight and higher compaction density, the pole piece containing hydroxyapatite inorganic fiber is prone to cracking after being folded in half and hot pressed, while the pole piece using the polymer material disclosed in the present invention is not easy to crack, which is unexpected.

[0197] Although the present disclosure has been described with reference to the embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present disclosure. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict. The present disclosure is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A lithium ion secondary battery electrode slurry, comprising an electrode material and a solvent, wherein the electrode material comprises an electrode active substance and a polymer additive, wherein the aspect ratio of the polymer additive is 500:1 to 50000:1, and the polymer additive is selected from one or more of polytetrafluoroethylene, polyethylene oxide, polyacrylonitrile, polyvinyl alcohol, polypyrrole, polythiophene and derivatives thereof.

2. The lithium-ion secondary battery pole piece slurry according to claim 1, wherein the aspect ratio of the polymer additive is 1000:1 to 50000:

1.

3. The lithium-ion secondary battery pole piece slurry according to claim 1, wherein the aspect ratio of the polymer additive is 5000:1 to 50000:

1. 4 . The lithium-ion secondary battery pole piece slurry according to claim 1 , wherein the aspect ratio of the polymer additive is 8000:1 to 50000:

1.

5. The lithium-ion secondary battery pole piece slurry according to any one of claims 1 to 4, wherein the electrode active material is selected from one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. 6 . The lithium-ion secondary battery pole piece slurry according to claim 1 , wherein the electrode material comprises 95-99.7 parts by weight of an electrode active substance and 0.1-1.0 parts by weight of a polymer additive. 7 . The lithium-ion secondary battery pole piece slurry according to claim 1 , wherein the slurry comprises 60-90 parts by weight of electrode material and 10-40 parts by weight of solvent.

8. A method for manufacturing the lithium ion secondary battery pole piece slurry according to any one of claims 1 to 7, comprising: mixing an electrode material with a solvent, wherein the electrode material comprises an electrode active substance and a polymer additive, The shear stirring is performed so that the polymer additive has an aspect ratio of 500:1 to 50000:

1.

9. A lithium-ion secondary battery electrode, comprising a current collector and an electrode material located on the current collector, wherein the electrode material comprises an electrode active substance and a polymer additive, wherein the polymer additive has an aspect ratio of 500:1 to 50000:1, and the polymer additive is selected from one or more of polytetrafluoroethylene, polyethylene oxide, polyacrylonitrile, polyvinyl alcohol, polypyrrole, polythiophene and their derivatives. 10 . The lithium ion secondary battery pole piece according to claim 9 , wherein the aspect ratio of the polymer additive is 1000:1 to 50000:

1. 11 . The lithium ion secondary battery pole piece according to claim 9 , wherein the aspect ratio of the polymer additive is 5000:1 to 50000:

1. 12 . The lithium-ion secondary battery pole piece according to claim 9 , wherein the aspect ratio of the polymer additive is 8000:1 to 50000:

1.

13. A lithium-ion secondary battery electrode according to any one of claims 9 to 12, wherein the current collector is aluminum foil; and the electrode active material is selected from one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. 14 . The lithium-ion secondary battery electrode according to claim 9 , wherein the electrode material comprises 93-99.5 parts by weight of the electrode active material and 0.1-1.0 parts by weight of the polymer additive. 15 . A method for preparing a lithium ion secondary battery pole piece according to any one of claims 9 to 14, comprising applying the lithium ion secondary battery pole piece slurry according to any one of claims 1 to 7 to a current collector.

16. A lithium-ion secondary battery, comprising the lithium-ion secondary battery pole piece according to any one of claims 9 to 14. 17 . A battery module comprising the lithium ion secondary battery according to claim 16 .

18. A battery pack comprising the battery module according to claim 17. 19 . An electrical device comprising at least one of the lithium-ion secondary battery of claim 16 , the battery module of claim 17 , and the battery pack of claim 18 .

Citation Information

Patent Citations

  • Lithium ion battery positive electrode piece preparation method and lithium ion battery

    CN108376761A

  • Lithium ion battery and positive pole piece

    CN110611117A